Mwcnt-Modified Electrode for Voltammetric Determination of Allura Red and Brilliant Blue Fcf in Isotonic Sport Drinks - Toledo-Neira, C; Toledo-Neira, C (Wiley-VCH Verlag, 2019)
A fast and simple electrochemical sensor is presented for the determination of allura red and brilliant blue in isotonic sport drinks, using a glassy carbon electrode modified with multi-walled carbon nanotubes. The electrochemical behavior of the colorants was studied by cyclic and differential pulse voltammetry in 0.1 M PBS, pH 7.0. The solution pH, the amount of nanomaterial on the surface of the electrode and the accumulation time of each colorant were optimized. Under the optimal conditions, the sensor exhibited a linear response to allura red and brilliant blue with detection limits of 7 μg L−1 and 52 μg L−1, respectively. The sensor was applied to the analysis of commercial isotonic sports drinks that contain individual or mixed colorants, showing good sensitivity and reproducibility. The results were compared with a chromatographic method showing that the levels of colorants are low and did not show a risk for a consumer s health. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim